Some of us are most at risk: Systematic review and meta-analysis of correlates of depressive symptoms among healthcare workers during the SARS-CoV-2 outbreak. (December 2021) - Crocamo, Cristina; Bachi, Bianca; Calabrese, Angela; Callovini, Tommaso; Cavaleri, Daniele; Cioni, Riccardo M.; Moretti, Federico; Bartoli, Francesco; Carrà, Giuseppe
Highlights: COVID-19 pandemic has been a major burden on healthcare workers' (HCWs) wellbeing. Early recognition of correlates of depressive symptoms among HCWs is pivotal. Some professional and individual/interpersonal factors identify vulnerable HCWs. Additional high-quality research on mental health burden among HCWs is needed. Tailored interventions would be instrumental for a second wave of the pandemic. Abstract: The COVID-19 pandemic has had a severe psychosocial impact on healthcare workers (HCWs). This systematic review and meta-analysis aimed at evaluating the association between individual features and depressive symptoms reported by HCWs during the pandemic. We searched Medline, Embase, and PsycInfo up to 23 June 2020. We included cross-sectional studies testing the association between individual correlates and depressive symptoms in HCWs during the SARS-CoV-2 outbreak. Fourteen studies met inclusion criteria, involving 14, 173 HCWs (3, 070 with depressive symptoms). Women (OR = 1.50; 95 %CI: 1.28–1.76; I 2 = 40.0 %), individuals with suspected/confirmed COVID-19 (OR = 2.10; 95 %CI: 1.64–2.69; I 2 = 0 %), and those with an infected family member or friend (OR = 1.67; 95 %CI: 1.37–2.04; I 2 = 0%) were more likely to report depressive features, which, instead, were less frequent among doctors (compared with nurses) (OR = 0.80; 95 %CI: 0.66–0.98; I 2 = 48.2 %) and HCWs who felt adequately protected (OR = 0.48; 95 %CI: 0.32–0.72; I 2 = 36.3 %). Our study provided timely evidence on the correlates of depressive symptoms among HCWs during the pandemic. Early screening is crucial to develop tailored health interventions, redesigning the response to COVID-19.